2019
DOI: 10.1186/s13256-019-2135-3
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic methotrexate-associated lymphoproliferative disorders identified by multiple liver tumors: a case report and review of the literature

Abstract: Background Methotrexate, an immunosuppressant, is widely used as the standard therapeutic drug for rheumatoid arthritis. With the increasing frequency of use of methotrexate, adverse effects of methotrexate have been reported, one of which is known as methotrexate-associated lymphoproliferative disorders. The etiology of hepatic methotrexate-associated lymphoproliferative disorders remains largely unknown. To date, there have only been ten cases of hepatic methotrexate-associated lymphoproliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Thus far, 16 cases with MTX-LPD in the liver have been reported ( 10 , 11 , 23 ), and the duration of MTX has ranged from 24 to 120 months. Therefore, the MTX duration of 17 years in the present case is the longest yet recorded.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus far, 16 cases with MTX-LPD in the liver have been reported ( 10 , 11 , 23 ), and the duration of MTX has ranged from 24 to 120 months. Therefore, the MTX duration of 17 years in the present case is the longest yet recorded.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding imaging findings, it was reported that liver tumors of MTX-LPD appeared as low-density areas on plain CT images and that most tumors were hypovascular on contrast-enhanced CT, although some showed mild ring enhancement ( 10 ). Because no typical imaging features of hepatic lymphoma have been reported, it is difficult to distinguish hepatic lymphoma from HCC or metastatic tumors based on imaging findings alone ( 11 ). Indeed, the present case showed early enhancement and wash-out in contrast-enhanced CT/MRI images, which are typical findings of HCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oebisu et al reported a case of MTX‐LPD with a pathological fracture of the femur, 5 and Kikuchi reported a case accompanied by a spinal lesion 6 . In addition, hepatic lesions rarely develop in patients with MTX‐LPD, with only 11 cases having been reported in the English literature to date 11 …”
Section: What Is New and Conclusionmentioning
confidence: 99%
“… 6 In addition, hepatic lesions rarely develop in patients with MTX‐LPD, with only 11 cases having been reported in the English literature to date. 11 …”
Section: What Is New and Conclusionmentioning
confidence: 99%